Customer Satisfaction with Islamic Banks: A Case Study of Al Rajhi Bank - Faten A. Al Dugaishem; M. Junaid Khawaja (Institute for Research and Community Empowerment (LPPM TAZKIA), 2017)
Abstract. This study aims to identify the factors that lead to the level of customer satisfaction about online services provided by Al Rajhi Bank, which is the largest Islamic Bank in the world. This study is conducted on a sample of customers who deal with Al Rajhi Bank in Qassim region, Saudi Arabia by measuring different constructs such as; reliability, efficiency, response, and empathy which have been taken as determinants of customer satisfaction. The sample size of the respondents is 184 clients. The study reveals that reliability, efficiency, response and empathy all have a positive and significant impact on customer satisfaction. In addition, the results also show that the dimension “efficiency” plays a leading role in the customer satisfaction. This means that indicators of efficiency like ease of service, diversity of online services, organized information and transactions in reasonable times frame are the most important factors in achieving customer satisfaction.